Efficient electrochemical production of glucaric acid and H2 via glucose electrolysis - Liu, Wu-Jun; Xu, Zhuoran; Zhao, Dongting; Pan, Xiao-Qiang; Li, Hong-Chao; Hu, Xiao; Fan, Zhi-Yong; Wang, Wei-Kang; Zhao, Guo-Hua; Jin, Song; Huber, George W.; Yu, Han-Qing (Nature communications, 2020)
Glucose electrolysis offers a prospect of value-added glucaric acid synthesis and energy-saving hydrogen production from the biomass-based platform molecules. Here we report that nanostructured NiFe oxide (NiFeO x ) and nitride (NiFeN x ) catalysts, synthesized from NiFe layered double hydroxide nanosheet arrays on three-dimensional Ni foams, demonstrate a high activity and selectivity towards anodic glucose oxidation. The electrolytic cell assembled with these two catalysts can deliver 100 mA cm −2 at 1.39 V. A faradaic efficiency of 87% and glucaric acid yield of 83% are obtained from the glucose electrolysis, which takes place via a guluronic acid pathway evidenced by in-situ infrared spectroscopy. A rigorous process model combined with a techno-economic analysis shows that the electrochemical reduction of glucose produces glucaric acid at a 54% lower cost than the current chemical approach. This work suggests that glucose electrolysis is an energy-saving and cost-effective approach for H 2 production and biomass valorization. Renewable biomass conversion may afford high-value products from common materials, but catalysts usually require expensive metals and exhibit poor selectivities. Here, authors employ nickel-iron oxide and nitride electrocatalysts to produce H 2 and to convert glucose to glucaric acid selectively.